Measurement and mitigation of greenhouse gases in African livestock systems: building capability to meet the challenge: Workshop Report - Silvestri, Silvia; Knox, D. (2012)
The International Livestock Research Institute (ILRI) hosted a 3-day workshop sponsored by the Government of New Zealand, ILRI, CCAFS in support of the objectives of the Livestock Research Group of the Global Research Alliance. The workshop on ‘Measurement and mitigation of greenhouse gases in African livestock systems: building capacity to meet the challenge’ took place on 24-26 September 2012 in Nairobi. Twenty participants representing Government, National Research Institutes and Universities from ten African countries participated in the workshop: Burkina Faso, Ethiopia, Ghana, Kenya, Mali, Niger, Senegal, South Africa, Tanzania, and Uganda.